A Multicentennial Proxy Record of Northeast Pacific Sea Surface Temperatures From the Annual Growth Increments of Panopea generosa. Issue 9 (14th September 2021) - Edge, David C.; Reynolds, David J.; Wanamaker, Alan D.; Griffin, Daniel; Bureau, Dominique; Outridge, Christine; Stevick, Bethany C.; Weng, Richard; Black, Bryan A.
Abstract: Growth‐increment widths of Pacific geoduck ( Panopea generosa ), a long‐lived bivalve, are used to develop the first marine‐based, multicentennial, annually resolved, and exactly dated archive of Northeast Pacific sea surface temperatures (SST). The chronology is sampled from the Tree Nob Islands, British Columbia, Canada, continuously covers 1725–2008, and also contains nine older radiocarbon‐dated segments, which together span 58% of the last 1, 500 years. Age‐related growth declines were removed by aligning all increments relative to age of increment formation and fitting with a single detrending curve to preserve low‐frequency signals. The geoduck chronology was used to reconstruct local SST variability across the seasonal window of April through November. The chronology at both the concurrent (lag‐0) and following (lag+1) year are both highly significant predictors of SST in a stepwise multiple linear regression, explaining 54% of the variance in the period of instrumental overlap (1940–2001), passing strict tests of calibration‐verification. Reconstructed SSTs contained significant spectral power at periods from 3 to 64 years, suggesting that 20th century variability in these periodicities is not unusual in the longer‐term context. The period of lowest growth coincided with the Dalton minimum, an episode of reduced solar irradiance from 1790–1830, as well as the 1809 Unknown eruption, suggesting that solar and volcanic signals are present in the SST history. The most conspicuous aspect of the reconstruction is the steady and unprecedented warming trend that began in the mid‐1800s and continues through present. The post‐1976 interval includes the two warmest decades of the reconstruction. Key Points: We develop the first marine‐based, multicentennial, annually resolved archive of Northeast Pacific sea surface temperatures (SST) The SST reconstruction captures 54% of instrumental variance and relates to radiative forcing and the El Niño Southern Oscillation The reconstruction captures a steady and unprecedented warming trend that began in the mid‐1800s and continues through present